A study of the impact of SETS-based multimedia assessment on students’ metacognitive abilities - Hidayati, Nuril; Safitri, Nur Lina; Triyandana , Arga; Prayitno , Trio Ageng; Nisa, Khoirun; Riyanto, Riyanto (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
There are difficulties in accustoming students to hone their metacognitive abilities in learning human anatomy and physiology in the era of the 4.0 revolution due to the lack of availability of SETS-based multimedia assessments. The purpose of this study was to analyze the effect of SETS-based multimedia assessments on students' metacognitive abilities. The research method was a quasi-experimental with a nonequivalent control group design pretest-posttest. The research sample was 2 classes (the experimental class was called A and the control class was called B) with 17 students in the experimental class, and 24 students in the control class in the Biology Education Study Program of IKIP Budi Utomo, who were taking the human anatomy and physiology course. The research instrument was pretest and posttest questions on the SETS-based multimedia assessment as many as 15 multiple-choice questions containing indicators of metacognitive abilities. The research data were in the form of pretest and posttest scores from the experimental class and the control class. The research data analysis technique used the Anacova test via SPSS for Windows. The results showed that SETS-based multimedia assessments affected students' metacognitive abilities (sig < 0.05). The study concludes that SETS-based multimedia assessment affects students' metacognitive abilities in human anatomy and physiology courses. The results of this study are recommended as assessment development materials to be integrated into the higher education curriculum as an effort to empower students' metacognitive abilities.